Kajian Geografis Pemetaan Risiko Bencana Banjir di Kawasan Transmigrasi Kecamatan Taluditi - Muhammad Rejki Zakaria; Daud Yusuf; Rakhmat Jaya Lahay (-, 2026)
This study was motivated by the high risk of flooding in the transmigration area of Taluditi Subdistrict, which is influenced by land-use changes, topographic conditions, and rainfall. This study aims to map flood risk levels and enhance community understanding of disaster mitigation. The methodology employed is a descriptive quantitative approach based on Geographic Information Systems (GIS), utilizing spatial analysis and SWOT analysis through field observations, questionnaires, and interviews. The research results indicate that high-risk areas are located in low-lying regions near river channels with inadequate drainage systems. Internally, the region possesses strengths in social aspects and natural resources, while externally, there are opportunities for government support despite facing the threat of climate change. These findings underscore the importance of integrating spatial analysis and community empowerment in sustainable disaster mitigation efforts.